Pengaruh Likuiditas, Solvabilitas, Manajemen Aset, Ukuran Perusahaan dan Komite Audit terhadap Kinerja Keuangan Perusahaan - Andi Faridl Haykal Artsam; Dista Amalia Arifah (Politeknik Raflesia Press, 2025)
Financial performance refers to the company's ability as shown in the financial statements used by stakeholders to make decisions. This study aims to examine the influence of liquidity, solvency, asset management, company size, and audit committee on financial performance in manufacturing companies in Indonesia. The population in this study consists of companies in the Chemical Industry, Consumer Goods Industry, and Miscellaneous Industry sectors that have been listed on the Indonesia Stock Exchange during the period 2018-2022. The sampling technique used was purposive sampling, and 340 samples were obtained. The analysis method used to test the hypothesis is multiple linear regression analysis. The results of this study indicate that the variables of liquidity, solvency, and audit committee have a negative and significant impact on financial performance, while the variables of asset management and company size have a positive and significant impact on financial performance in manufacturing companies in Indonesia.